Hydrodynamics of inverse liquid-solid circulating fluidized bed. (2nd February 2022) - Nan, Tian; Zhu, Jesse
Graphical abstract: Highlights: Hydrodynamics of ILSCFB is studied with 5 types of low-density particles. Axial and radial solids holdup distributions are generally uniform in ILSCFB. Flow structure in ILSCFB mirrors upright LSCFB. Slip velocity in ILSCFB is greater than U t due to clustering effect. Modified Richardson-Zaki equation is developed to predict solids holdup in ILSCFB. Abstract: Hydrodynamics of inverse liquid–solid circulating fluidized bed (ILSCFB) is comprehensively studied with five types of low-density particles in a long experimental column of 5.4 m tall. The flow patterns observed mirror those of upright LSCFB under similar conditions. Axial distribution of solids holdup is uniform and radial solids holdup is also generally uniform but with some dilute region existing near the wall. The average solids holdup increases with U s while decreases with U l . The effect of particle properties on the fluidization appears to be less extensive. The relationship between slip velocity and solids holdup in ILSCFB and inverse conventional fluidized bed is different. Clustering effect in liquid–solid circulating fluidized beds is first investigated. Particles with small particle Reynolds number tend to have more severe clustering as shown by the higher slip velocity. A modified Richardson-Zaki equation is developed for the prediction of solids holdup in inverse liquid–solid circulating fluidized bed.